Distance Education Course “Water as an Interdisciplinary Element of Teaching in Schools”: Action in Basic Education Through a Partnership between the PROFCIAMB Network and ANA, Brazil - da Rocha, Helena Midori Kashiwagi; Cavalcante, Katia Viana; Costa, Valéria Sandra de Oliveira; Malheiros, Tadeu Fabricio; Krëmpi, Daniela Alessandra (Universitas Diponegoro, 2023)
The Graduate Program in the National Network for Teaching Environmental Sciences (PROFCIAMB) in partnership with the National Water and Basic Sanitation Agency (ANA) and the Coordination for the Improvement of Higher Education Personnel (CAPES) updated the educational material of the “Water in Course – Multipliers” associated with the collection of didactic products desenvolved with the theme of Water by ANA to compose the education distance course “Water as an Interdisciplinary Element of Teaching in Schools”, which is aimed at teachers of Basic Education and professionals who work with teaching in non-formal spaces and/or non-school. Its objectives were built considering the Sustainable Development Goals ODS4 Quality Education and ODS6 Potable Water and Sanitation. The course was supported by Tutors (Students from the PROFCIAMB Network) and had a workload of 80 hours, distributed over four months in 5 modules. Module 1 to 4 for the Water and Teaching Principles and Methodology disciplines: Water: sustainable consumption and its multiple uses; Situation of water resources in Brazil; All together by the water; and, Cases of success in water care. Module 5 for the Application of learning discipline (lesson plan elaboration and lesson plan report). Four classes were offered from 2018 to 2022 with 4,645 vacancies and 14,850 registered candidates, nationwide course; 4,518 students enrollments and 1,656 students approved.